Future (post-COVID) digital, smart and sustainable cities in the wake of 6G: Digital twins, immersive realities and new urban economies - Allam, Zaheer; Jones, David S. (Land use policy, 2021)
•Explores the emerging subject of 6G and its associated concepts.•Dwells into the application of 6G in cities and its challenges.•Underlines future prospects of 6G to unpack the tenets of SDG 11.•Explore how 6G will better help a technological revolution and support the Smart City Movement. With the advance of 5G technologies by both academia and industry, 5G adoption is gaining widespread acceptance in numerous cities, prompting further innovations in Smart City technologies riding on the wave of the Internet of Things (IoT). However, even in its infancy stage, the speed of technological advancement is already highlighting the limitations of 5G, and its potentially short lifespan as new technologies are rendered obsolete faster. This fast-moving field is coupled with an ongoing and increasing funding into Research & Development (R&D) efforts by private corporations, to potentially commercialise on the surge in demand for ‘smarter’ cities’, This paper aims to chart the major directions and scope emerging dimensions inherent to 6G technology, including Digital Twins and Immersive Realities (XR) that, when applied to cities that are currently being equipped with digital infrastructural backbones, may have direct socio-economic impacts upon our lives while responding to the tenets of the Sustainable Development Goal 11. Looking at the future 6G technology this article considers the prospects of 6G, and its associated concepts, and its relations as they pertain to Future, Smart, Digital and Sustainable Cities.